Students’ Communication Strategies in Performing Transactional Task through CLIL Approach - Dodi Settiawan (Nalar Global Foundation, 2021)
At higher education level, student achievement is highly dependent on their ability to master scientific content through English as the language of instruction. As a result of this paradigm, content and language integrated learning (CLIL) is implemented. In addition to the four language skills, CLIL also emphasizes mastery of content which is also a pillar of communicative competence. Thus, students’ transactional competence needs to be developed as an extension of interactional competence. The research described in this article was carried out to better understand communicative competence by testing transactional competence through the linkage of content mastery and the use of communication strategies in the form of task-based communication. By implementing the CLIL approach, this study explains how task-based content and language teaching can be used in explicit instruction during the development of student communication strategies. The research focused on communication strategies such as asking for clarification, imitation, checking understanding and maintenance strategies such as giving confirmation. The results show that empowering students to be able to maintain communication plays the most significant role in improving task-based learning outcomes. The tests showed that the communication strategies used by the students resulted in a significant improvement in their test scores and willingness to perform transactional tasks. The explicit instruction regarding the use of communication strategies in performing transactional tasks also indicates that opportunities for further research and application exist in the specific contexts of other faculties using content and language integrated learning where transactional competencies are critical for their students' future work.